Praktikalitas E-Book Edupark IPA dengan Pendekatan Saintifik Berdasarkan Destinasi Wisata Pantai Padang - Elvisa, Gita Oktia; Rifai, Hamdi (Universitas Negeri Padang, 2021)
Learning that is carried out in the world of education is currently running on new policies by implementing the 2013 curriculum education system which is rooted in local and national culture, which means that it must provide opportunities for students to learn according to the needs and potential of their respective regions so that students can take advantage of it. technology in the learning process, thus education will continue to progress and develop. One of the teaching materials that can be made following the 2013 Curriculum under regional potential and utilizing technology is the edupark e-book. This study aims to produce a practical science edupark e-book. The type of research used is Design Research with the type of Development Studies using the Plomp model with the Preliminary Research, Development or Prototyping Phase, and Assessment Phase stages. The instrument in this study was a practicality sheet, namely a questionnaire on the responses of educators and students. The practical analysis technique of the science edupark e-book uses a Likert scale with 4 assessment categories. The e-book practicality questionnaire includes the following 4 aspects: (a) usable; (b) Easy to use (c) Appealing and; (d) Efficient. It can be concluded that the IPA edupark E-book with a scientific approach based on Padang Beach tourist destinations meets very practical criteria for all practical aspects.Keywords : E-book, Edupark, Scientific Approach, Practicality